GAPO syndrome in seven new patients: Identification of five novel ANTXR1 mutations including the first large intragenic deletion. Issue 2 (21st December 2018) - Abdel‐Hamid, Mohamed S.; Ismail, Samira; Zaki, Maha S.; Abdel‐Salam, Ghada M. H.; Otaify, Ghada A.; Issa, Mahmoud Y.; Abdel‐Kader, Mohamed; Girgis, Marian; Aboul‐Ezz, Eman; Mazen, Inas; Aglan, Mona S.; Temtamy, Samia A.
Abstract : GAPO syndrome is a very rare disorder characterized by growth retardation, alopecia, pseudoanodontia and progressive optic atrophy. It is caused by biallelic mutations in the ANTXR1 gene. Herein, we describe the clinical and molecular findings of seven new patients with GAPO syndrome. Our patients presented with the characteristic clinical features of the syndrome except for one patient who did not display total alopecia till the age of two years. Strikingly, optic atrophy and glaucoma were observed in all patients and one patient showed keratopathy in addition. Moreover, craniosynstosis was an unusual associated finding in one patient. Mutational analysis of ANTXR1 gene identified five novel homozygous mutations including two frameshift, two splice site and a large intragenic deletion of exon 3. Our results reinforce the clinical characteristics of the syndrome, expand the mutational spectrum and provide more insights into the role of the ANTXR1 protein in the regulation of extracellular matrix.